2005
DOI: 10.1128/jcm.43.1.95-100.2005
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of the Beijing Family Genotypes of Mycobacterium tuberculosis in Taiwan

Abstract: To investigate the distribution of the Beijing family genotypes of Mycobacterium tuberculosis in Taiwan, we collected 421 M. tuberculosis complex clinical isolates at random from four geographic regions of Taiwan and analyzed them by spacer oligonucleotide typing (spoligotyping) in 2003. We found 113 resolved spoligotypes, among which we identified 28 (24.8%) clusters. One hundred eighty-seven (44.4%) isolates were Beijing family genotypes and consisted of 172 (40.9%) characteristic Beijing genotypes and 15 (3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
24
1
1

Year Published

2005
2005
2014
2014

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 53 publications
(31 citation statements)
references
References 34 publications
5
24
1
1
Order By: Relevance
“…Excluding the Beijing genotype and three Beijing-like strains, the diversity observed was limited to seven clusters (18.8% of the strains): EAI2-Manilla, Haarlem3, LAM9-var, T1, T1-var, T2, and T3-Osaka. The high percentage of Beijing strains in Okinawa (71.3%) is in agreement with the overall value of 60% reported for East Asian countries (9) but remains one of the highest in this region (23,24,26), with percentages varying from 90% in Beijing and the Hebei province of China (11) to 70% in Korea (24), 68% in Hong Kong (16) and Thailand (25), 54% in Vietnam (1), 44% in Taiwan (14), 33% in peninsular Malaysia (6), and 11% in eastern Malaysia (6). On the other hand, the low proportion of LAM and Haarlem in this study shows the nonexposition of this insular population to any migratory flux from Latin American and European countries.…”
Section: Discussionsupporting
confidence: 74%
“…Excluding the Beijing genotype and three Beijing-like strains, the diversity observed was limited to seven clusters (18.8% of the strains): EAI2-Manilla, Haarlem3, LAM9-var, T1, T1-var, T2, and T3-Osaka. The high percentage of Beijing strains in Okinawa (71.3%) is in agreement with the overall value of 60% reported for East Asian countries (9) but remains one of the highest in this region (23,24,26), with percentages varying from 90% in Beijing and the Hebei province of China (11) to 70% in Korea (24), 68% in Hong Kong (16) and Thailand (25), 54% in Vietnam (1), 44% in Taiwan (14), 33% in peninsular Malaysia (6), and 11% in eastern Malaysia (6). On the other hand, the low proportion of LAM and Haarlem in this study shows the nonexposition of this insular population to any migratory flux from Latin American and European countries.…”
Section: Discussionsupporting
confidence: 74%
“…This genotype is thought to be associated with drug resistance (1,10,23,41). However, less association has been reported in other geographic settings (2,3,20,43). In the present study, the statistical analysis showed that there was no difference between the Beijing and non-Beijing genotype strains in drug resistance patterns, indicating that the Beijing genotype is less likely to be associated with the high prevalence of drug resistance and M. tuberculosis TB in our area.…”
Section: Discussionmentioning
confidence: 44%
“…According to the present data, the impact of the Beijing strain in 2-month sputum culture conversion is probably limited in Taiwan. However, previous studies have documented that the Beijing strain, in Taiwan, is not associated with a significantly higher resistance rate to rifampicin, which may lead to its nonsignificant role in culture conversion [21,23]. In areas where the Beijing strain has been reported to have a higher drug-resistance rate, especially to rifampicin, the role of genotyping in culture conversion remains to be identified and further studies are needed to clarify the issue.…”
Section: Discussionmentioning
confidence: 79%